Different phenotypes of drug-induced anaphylaxis-Data from the European Anaphylaxis Registry - Hanschmann, Theresa; Francuzik, Wojciech; Doelle-Bierke, Sabine; Hofmeier, Kathrin Scherer; Grabenhenrich, Linus; Rueff, Franziska; Renaudin, Jean-Marie; Pfoehler, Claudia; Treudler, Regina; Bilo, M. Beatrice; Lang, Roland; Ensina, Luis Felipe; et al. (Allergy, 2022)
BackgroundDrugs are a frequent cause of severe anaphylactic reactions. Here, we analyze a large dataset on drug induced anaphylaxis regarding elicitors, risk factors, symptoms, and treatment. MethodsData from the European Anaphylaxis Registry (2007-2019) with 1815 reported cases of drug-induced anaphylaxis were studied accordingly. ResultsDrugs are the third most frequent cause of anaphylaxis reported in the Anaphylaxis Registry. Among the eliciting groups of drugs analgesics and antibiotics were far most often reported. Female and senior patients were more frequently affected, while the number of children with DIA was low. DIA patients had symptoms affecting the skin and mucous membranes (n = 1525, 84.02%), the respiratory (n = 1300, 71.63%), the cardiovascular (n = 1251, 68.93%) and the gastrointestinal system (n = 549, 30.25%). Drugs caused significant more severe reactions, occurred more often in medical facilities and led to increased hospitalization rates in comparison to food and insect venom induced anaphylaxis. Adrenaline was used more often in patients with DIA than in anaphylaxis due to other causes. Patients with skin symptoms received more antihistamines and corticosteroids in the acute treatment, while gastrointestinal symptoms led to less adrenaline use. ConclusionThe study contributes to a better understanding of DIA, with a large number of cases from Europe supporting previous data, e.g., analgesics and antibiotics being the most frequent culprits for DIA. Female gender and higher age are relevant risk factors and despite clear recommendations, the emergency treatment of DIA is not administered according to the guidelines.
CRIS-Team WoS Importer:2023-01-20